New records of Copidognathus mites (Acari: Halacaridae) from mangroves in Brunei Darussalam with descriptions of two new species - Chatterjee, Tapas; Marshall, David J; Pešić, Vladimir (Zootaxa, 2012)
Three species of the genus Copidognathus were collected from the algal cover of mangrove pneumatophores in BruneiDarussalam. Two of the species are new and are described as Copidognathus mangrovorum and C. bruneiensis. C. rhombognathoideus Bartsch is reported for the first time from Brunei Darussalam.